Experimental investigation on the effects of biomimetic surface roughness on swept back tapered NACA 4412 wing - Malik, Khurshid (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
This dissertation studies the overall pros and cons of surface roughness elements over a NACA 4412 tapered, swept back wing with a dihedral of 5°and a sweep angle of 30°. The tests were conducted at a Reynolds number of 4x10⁵ with and without roughness elements in the IIUM Low Speed wind tunnel. Different roughness sizes and roughness locations were tested for a range of angle of attack. Lift, drag and pitching moment coefficients were measured for the wing with smooth and surface roughness elements.As the surface roughness increases, the drag increases due to the increase in skin friction and the lift decreases. Flexible roughness element FRE1 shows highest increase in drag coefficient by 151% in the total drag compared to the smooth wing. The lowest increment in drag coefficient is 1.8% for roughness element SRE4 compared to the smooth element. In the case of cylindrical roughness elements, CRE8 showed the highest increment in drag coefficient and CRE3 showed the lowest increment in the drag. The highest lift coefficient obtained for the wing with surface roughness is for the SRE4 type of roughness element. Roughness elements CRE1, CRE4 & FRE1 show a 4% decline in total lift compared to the smooth wing. Surface roughness is seen to delay the stall angle. For roughness elements SRE1, SRE2, SRE3, CRE4 and CRE5, the highest stall angle is delayed by 4o compared to the clean wing. There is no effect on stall angle for roughness element CRE6. The wing element with the roughness located at 95% of the mean chord from the leading edge shows minimum drag and maximum lift compared to the other locations. Lift to drag ratio is highest for smooth wing compared to wing with any other roughness element. Cylindrical roughness element CRE5 displays lowest L/D ratio by a decrement of approximately 55% compared to the smooth wing. The element SRE4 shows highest L/D ratio with a decrement of approximately 7% compared to the clean wing. The behavior of stability can be tested by considering the increment in pitching moment coefficient with change in angle of attack. No significant effect on stability was found after installing roughness elements on wing. The pitching moment coefficient was found to be higher for flexible roughness elements. In case of rigid surface roughness, there is no significant effect on the pitching moment. Therefore, the smooth surface wing is the more efficient compared to the wing with roughness elements. And as the roughness size increases, the efficiency of the wing decreases. After applying roughness elements on the smooth wing, however, efficiency of wing is declined, but stall angle is delayed at this Reynolds number of 4x10⁵.